Imre Festetics and the Sheep Breeders' Society of Moravia: Mendel's Forgotten “Research Network” - Poczai, Péter; Bell, Neil; Hyvönen, Jaakko (PLOS Biology, 2014)
Poczai and coauthors introduce us to a Moravian Count, Imre Festetics, who formulated many principles of genetics before Mendel was born and helped establish the “research network” within which Mendel later developed his own ideas.